The effects of acute glucoprivation on adrenomedullary function in SHR and WKY rats - Hanafi Ahmad Damanhuri,; Dunkley, Peter Robert; Goodchild, Ann Kathleen (Penerbit Universiti Kebangsaan Malaysia, 2021)
We have shown previously, acute intraperitoneal administration of 2-deoxy-d-glucose (2DG) into Sprague-Dawley rats led to activation of the adrenal medulla chromaffin cells, indicated with increased protein kinase activity and increased tyrosine hydroxylase (TH) phosphorylation, as well as increased plasma adrenaline and glucose levels. Here we have used spontaneous hypertensive (SHR) and Wistar Kyoto (WKY) rats to investigate whether hypertension alters basal adrenal chromaffin cell function, or the response of these cells to acute 2DG treatment. At basal level, we found no differences in adrenal medulla TH protein, TH phosphorylation, TH activity or catecholamine levels between SHR and WKY despite a significant difference in the level of systolic blood pressure; nor were there differences in plasma catecholamine levels or blood glucose (BG). Furthermore, the vehicle animals evoked no significant changes in any parameter measured in SHR, but evoked significant increases in pSer19TH, plasma adrenaline and BG in WKY. Single episode of glucoprivation evoked increases in PKA and CDK/MAPK, pSer40TH, pSer31TH, TH activity, and plasma adrenaline and BG in SHR, and in addition evoked increases in PKC, CAMKII, and pSer19TH in WKY. These findings are significant which indicates hypertension does not impact catecholamine function in the adrenal gland. It also appears that hypertension does not alter the adrenal response to glucoprivation. The findings are also significant as WKY showed greater adrenal activation of protein kinases and TH phosphorylation in response to saline and 2DG when compared to SHR and possible reasons for these findings are further discussed.